2002
DOI: 10.1099/00221287-148-6-1627
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Streptococcus gordonii SspB protein in the development of Porphyromonas gingivalis biofilms on streptococcal substrates

Abstract: Porphyromonas gingivalis is an aggressive periodontal pathogen that persists in the mixed-species plaque biofilm on tooth surfaces. P. gingivalis cells attach to the plaque commensal Streptococcus gordonii and this coadhesion event leads to the development of P. gingivalis biofilms. Binding of these organisms is multimodal, involving both the P. gingivalis major fimbrial FimA protein and the species-specific interaction of the minor fimbrial Mfa1 protein with the streptococcal SspB protein. This study examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
181
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 42 publications
5
181
1
Order By: Relevance
“…Fluid-phase gp340, in saliva and other mucosal secretions, agglutinates microbes for clearance from the body, whereas solid-phase gp340 adsorbed onto host surfaces provides a substratum for microbial adherence (18). AgI/II family polypeptides have also been shown to promote microbial community development by binding to oral bacteria Actinomyces oris (19 -21) or Porphyromonas gingivalis (22,23), as well as to the pathogenic fungus Candida albicans (24). More recently, an AgI/II family polypeptide (group A Streptococcus surface protein, AspA) has been described in group A Streptococcus (GAS) (25).…”
mentioning
confidence: 99%
“…Fluid-phase gp340, in saliva and other mucosal secretions, agglutinates microbes for clearance from the body, whereas solid-phase gp340 adsorbed onto host surfaces provides a substratum for microbial adherence (18). AgI/II family polypeptides have also been shown to promote microbial community development by binding to oral bacteria Actinomyces oris (19 -21) or Porphyromonas gingivalis (22,23), as well as to the pathogenic fungus Candida albicans (24). More recently, an AgI/II family polypeptide (group A Streptococcus surface protein, AspA) has been described in group A Streptococcus (GAS) (25).…”
mentioning
confidence: 99%
“…Although the role of minor fimbriae in P. gingivalis virulence is less well understood, Hiramine et al (6) have shown that the 67-kDa fimbrial protein induces IL-1␣, IL-1␤, and tumor necrosis factor alpha expression in mouse peritoneal macrophages, suggesting their possible involvement in the inflammatory response during the development of periodontal disease. Recent research has shown that minor fimbriae are necessary for the development of P. gingivalis biofilms on streptococcal substrates (7). Coadhesion of P. gingivalis-Streptococcus gordonii requires specific recognition between the 67-kDa and SspB proteins.…”
mentioning
confidence: 99%
“…These intergeneric coadhesion events have been implicated in various aspects of the formation of complex oral microbial biofilms, including the structure, nutritional symbiosis, interspecies communication, and sharing of genetic material (25,26,38,40,41). It is clear from the literature that a number of the species that were employed in developing these biofilms have the potential to coaggregate; however, there are no direct data for some of the strains that were used (5,15,26,28). One study by Foster and Kolenbrander (15) suggested that with Veillonella atypica and A. naeslundii, coaggregation in the planktonic phase affected biofilm formation.…”
Section: Discussionmentioning
confidence: 90%